Health Risks Assessment of Metal Exposure from a Tropical Semi-urban Soil. Issue 1 (2nd January 2020) - Sulaiman, Fazrul Razman; Mohd Ghazali, Fatehah; Ismail, Ismaniza
ABSTRACT: The concentrations of metals (Cr, Pb, Zn) in the suburban soil of Jengka, Malaysia and their potential risks to human health have been determined. This study estimated both carcinogenic and non-carcinogenic risks using the hazard index (HI) and lifetime cancer risk (LCR). The mean concentrations of metal were dominated by Zn (85.91 mg/kg), followed by Pb (38.50 mg/kg) and Cr (26.24 mg/kg). The enrichment factor (EF) and geo-accumulation index (Igeo) suggested the enrichment of Cr, despite its lowest mean concentration. The HI values of metal for non-carcinogenic risks were in the order of Cr>Pb>Zn. For cancer risk, the LCR values for Cr of Jengka semi-urban soil were slightly higher (6.16E-4) than the acceptable LCR limits (1E-5). Dermal contact was the main route for both cancer and non-cancer risks. Cement work from construction sites and road dust were found to be having high metal exposure in corresponding to health risk assessments, particularly for sampling point adjacent to the entrance of residential construction areas. Therefore, preventive actions are necessary to minimize the health risks in the long term, especially for construction areas.